Factors Affecting The Occurrence Of Pregnant Women Diabetes Mellitus Gestational - Linda Yanti; Surtiningsih Surtiningsih (Viva Medika, 2016)
Diabetes mellitus in pregnancy will cause a bad influence on the mother, among others, withhidramnion pregnancy, toxemia gravidarum, infection, and ketoacidosis. The effect on thechildren, is a congenital disorder, respiratory failure syndrome, fetal death in utero,hyperbilirubinemia, macrosomia, hypoglycemia, and hypocalcemia. On labor may occur atonicuterus, uterine inseria, shoulder dystocia, stillbirth, termination of labor with action. This studyaims to identify factors that influence maternal whether the occurrence of gestational diabetesmellitus. This study was an observational analytic study with case control method, the entire population ispregnant women who visited the hospital Goeteng Tarunadibrata Purbalingga in 2015. Thesample in this study were all pregnant women aged over 24 weeks of pregnancy were divided intogroups of cases are mothers pregnant gestational diabetes and control groups, namely pregnantwomen who did not have gestational diabetes. The sample size in this study was calculated usingthe formula rule of thumb and diadaptkan each group of 50 samples. Data were analyzed usingChi-square test. The results showed factors parity over a significantly (p <0.005) risk 3,622 times the incidence ofgestational diabetes mellitus, factor the number of pregnancies was significantly (p <0.005) at riskof 4.827 times the incidence of gestational diabetes mellitus, obesity factor did not have asignificant influence (p> 0.005) on the incidence of gestational diabetes mellitus, factors ofrecurrent infections was significantly (p <0.005) risk 3,273 times the incidence of gestationaldiabetes mellitus, factor family history of diabetes was significantly (p <0.005) risk 2,935 timesthe incidence of gestational diabetes mellitus Keywords: Factors pregnant women, gestational diabetes